„Polski” Rilke - Kałążny, Jerzy (My University, 2012)
The publication of Katarzyna Kuczyńska-Koschany’s book "Rycerz i Śmierć. O Elegiach duinejskich Rainera Marii Rilkego" fills the large gap in Polish research on Rilke as it is the first monographic study of the "Duino elegies". The author of the book interprets individual elegies and discusses their mutual relationships within the whole of the cycle in a very personal way, appealing to her own reading and poetical sensibility. Simultaneously, the author supports her analysis with the theoretical foundations created by acclaimed and reputed German researchers of Rilke’s literary output such as Käte Hamburger, Beda Allemann, Manfred Engel and Jacob Steiner, among others. In her considerations, the author also refers to Polish translation of the elegies, notably those made by Mieczysław Jastrun and Adam Pomorski, also providing their critical interpretation.
“Polish” Rilke
Keywords: Rainer Maria Rilke; lyric poetry of the 20th century; elegy